2016
DOI: 10.1080/02699206.2016.1188422
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic language impairment in children with Noonan syndrome

Abstract: Noonan syndrome (NS) is a disorder causing symptoms like short stature, characteristic facial features, congenital heart disease, possible mental retardation, and pragmatic difficulties. This study describes the pragmatic skills in NS and discusses the linguistic profile of 17 informants aged 6–15 years, by comparing the participants’ scores on the Children’s Communication Checklist, 2nd edition (CCC-2) (Bishop, 2011), with a group of typically developing children of matching age and gender. Language impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Many children with NF1 or NS have speech articulation difficulties, and approximately 30% of children with NS [ 22 ] and 23–37% of children with NF1 [ 24 , 43 ] demonstrate impairment on gold-standard measures of language functioning. Parent rating measures indicate that children with NS are at increased risk for pragmatic communication problems relative to unaffected children [ 22 , 23 ] including skills such as interpreting gestures and facial expressions, understanding conversational conventions and making inferences about meaning in language based on context. On more direct, objective measures, individuals with NS or NF1 have been found to have more difficulties than unaffected peers with regard to perception and identification of emotional expression in faces [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many children with NF1 or NS have speech articulation difficulties, and approximately 30% of children with NS [ 22 ] and 23–37% of children with NF1 [ 24 , 43 ] demonstrate impairment on gold-standard measures of language functioning. Parent rating measures indicate that children with NS are at increased risk for pragmatic communication problems relative to unaffected children [ 22 , 23 ] including skills such as interpreting gestures and facial expressions, understanding conversational conventions and making inferences about meaning in language based on context. On more direct, objective measures, individuals with NS or NF1 have been found to have more difficulties than unaffected peers with regard to perception and identification of emotional expression in faces [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies reported pragmatic language impairment [PLI] in children with NS. People with PLI have difficulties in understanding and adapting to the needs of their conversational partners [33].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment and work of a speech therapist are also necessary due to disturbances in the development of communication competencies [19,20]. As shown in a previous study, children, and adolescents with NS do not have a single consistent pragmatic profile; however, 76.5% of participants in a study of pragmatic speech disorders showed communication disorders, and the pragmatic ability of children with NS was significantly lower than in the control group [21].…”
Section: Discussionmentioning
confidence: 96%